Implementation of Occupational Safety and Health Management System (SMK3) Through Lean Construction Method - Soeharto, M. Elbet; Amin, Mawardi (Riviera Publishing, 2025)
This study aims to analyze the implementation of building construction projects in the implementation of SMK3 using the Lean Construction (LC) method. The urgency of the study was to review the implementation of safe and correct work procedures in construction work projects carried out in building construction. The main purpose of implementing this method is to optimize financial operations, prevent loss of time, and minimize work accidents that result in waste through prevention efforts by considering various triggers as applied in the LC technique. The research method is carried out using a mixed-methods approach. The sample in the study includes 5 construction buildings, and 5 sources to obtain interview data. The LC implementation approach to SMK 3 is carried out through the 5S management system and the Last Planner System (LPS). The results of the study indicate that the planning carried out encompasses several aspects, including team socialization implementation. The results obtained were that construction projects carried out through the LC method, through the 5S management system approach, and LPS were proven to be able to optimize and make construction projects work effectively. The evaluation revealed that the evaluation process carried out by PT utilizes risk management and RIMS (Risk Management Plan), and has the potential to minimize the risk of loss and work-related accidents in construction projects.